Re-distributed manufacturing and the food-water-energy nexus: opportunities and challenges. Issue 7 (19th May 2019) - Veldhuis, Anton Johannes; Glover, Jane; Bradley, David; Behzadian, Kourosh; López-Avilés, Alma; Cottee, Julian; Downing, Clare; Ingram, John; Leach, Matthew; Farmani, Raziyeh; Butler, David; Pike, Andy; et al.
Abstract: Addressing the intersection of two important emerging research areas, re-distributed manufacturing (RDM) and the food-energy-water (FEW) nexus, this work combines insights from engineering, business and policy perspectives and explores opportunities and challenges towards a more localized and sustainable food system. Analysis centred on two specific food products, namely bread and tomato paste reveals that the feasibility and potential of RDM vary with the type of food product and the supply chain (SC) components. Physically, energy efficiency, water consumption and reduction of waste and carbon footprint may be affected by scale and location of production activities and potentials of industrial symbiosis. From the business perspective, novel products, new markets and new business models are expected in order for food RDM to penetrate within the established food industry. Studies on policies, through the lens of public procurement, call for solid evidence of envisioned environmental, social and economic benefits of a more localized food system. An initial integrated framework is proposed for understanding and assessing food RDM and the FEW nexus.